Annual Plan 1995-96 Tripura State Part II (Statements) - Planning Commission (Planning Commission, 1995)
Sectoral Outlay for Eighth Plan, Revived Outlay for Annual Plan 1994-95 and Proposed Outlay for 1995-96.
Planning and Coordination Department, Government of Tripura